Intervención nutricional a pacientes con pancreatitis aguda severa. Colecistitis crónica calculosa y diabetes mellitus tipo 2 - Diaz Muñoz, Mileydi Priscila (2022)
Hepatobiliary and pancreatic diseases represent a public health problem, affecting a high percentage of people in the world population. According to the World Health Organization (WHO), 400 million people in the world and 62 million in the Americas suffer from hepatobiliary and pancreatic diseases, the most frequent being type 2 diabetes mellitus and chronic calculous cholecystitis. Chronic calculous cholecystitis, pancreatitis and type 2 diabetes mellitus are digestive diseases that represent the main reasons for medical and nutritional consultation, caused by multiple factors associated with specific physiology and associated pathologies, as well as the genetic load of people and environmental factors.; being the main ones related to food; excess consumption of sugars, fatty foods with high cholesterol content and lack of physical activity. The timely diagnosis of these pathologies, as well as medical and nutritional therapy, will focus on the implementation of changes in habits and lifestyle, related to the main risk factors, being crucial the modification of the diet, in order to avoid and/or delay the appearance of associated complications.